(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the interconnection between sociolinguistics and psychology, two disciplines that intersect in their exploration of language, social behavior, and cognition. Topics such as language acquisition, identity formation, social interaction, and language variation are explored from an interdisciplinary perspective, showcasing the collaborative efforts of sociolinguists and psychologists in unraveling the complexities of language and its impact on individuals and society.